Synthesis and characterization of POSS hybrid organogels using Menschutkin quaternization chemistry - Kilic, Deniz; Balta, Demet Karaca; Saloglu, Didem; Temel, Gokhan (WILEY, 2019)
The present research describes a series of organic-inorganic hybrid gels based on polystyrene and polyhedral oligomeric silsesquioxanes (POSSs) prepared using free radical copolymerization and Menschutkin chemistry techniques. In the first step, poly(styrene-co-chloromethylstyrene) is readily achieved by thermally initiated radical copolymerization and the subsequently obtained copolymer reacts with diethanolamine functional POSS nanoparticles which are employed as the crosslinker. The resulting hybrid network possesses ionic moieties and inorganic POSS nanoparticles. The POSS-containing hybrid gels exhibit excellent organic solvent absorption and show good mechanical behaviour. Gel containing 0.8 x 10(-3) mmol of POSS(DEA)(8) (DEA, diethanolamine) reached the highest swelling ratio; hence, the corresponding gel can absorb organic solvent up to 20x its weight. The rate constant, coefficients and diffusional behaviour of hybrid organogels in organic solvent were examined as well. The organic solvent intake of the hybrid gel follows a non-Fickian type diffusion. (c) 2018 Society of Chemical Industry
Keywords: silsesquioxane; POSS; organogel; hybrid materials; quaternization; kinetics; HYDROGELS; COPOLYMERIZATION; NANOCOMPOSITES; Polymer Science